若x,y,z成等差数列,则(Z-X)^2-4(X-Y)(Y-Z)等于

来源:学生作业帮助网 编辑:作业帮 时间:2024/07/04 19:58:35
若x,y,z成等差数列,则(Z-X)^2-4(X-Y)(Y-Z)等于
x){ѽBRYDŽk;n_lꆧuv|#J78#] 'B72"u 'l)7DΆJnѨҭҨЭԨԭ#%@t4X6HflX\P,d&7 (o&ѯ 3@MJ&է:^ QkkVG!Jy6g66yvs7l|nOvX~yټH>c& f VJH+ jbB.

若x,y,z成等差数列,则(Z-X)^2-4(X-Y)(Y-Z)等于
若x,y,z成等差数列,则(Z-X)^2-4(X-Y)(Y-Z)等于

若x,y,z成等差数列,则(Z-X)^2-4(X-Y)(Y-Z)等于
(z-x)^2-4(x-y)(y-z)
(z-x)^2=(x-z)^2=[(x-y)+(y-z)]^2
[(x-y)+(y+z)]^2-4(x-y)(y-z)
(x-y)^2+(y-z)^2-2(x-y)(y-z)
[(x-y)-(y-z)]^2=0
(x+z-2y)^2=0
x,y,z成等差数列,所以x+z-2y=0
(Z-X)^2-4(X-Y)(Y-Z)等于0
希望采纳····

0
就算不去计算,,猜都猜的到。。

z-x)^2-4(x-y)(y-z)
(z-x)^2=(x-z)^2=[(x-y)+(y-z)]^2
[(x-y)+(y+z)]^2-4(x-y)(y-z)
(x-y)^2+(y-z)^2-2(x-y)(y-z)
[(x-y)-(y-z)]^2=0
(x+z-2y)^2=0